A Comparison of Electric Field Treatments to Hydropriming on Cucumber Seed Germination Enhancement - Rukui Huang; Sutevee Sukprakarn; Lop Phavaphutanon; Sunanta Juntakool; Chaiwat Chaikul (Agriculture and Natural Resources, 2006)
Three cucumber seed lots: ‘Bingo I’, ‘Bingo II’ and ‘HB128’ were subjected to hydropriming and electric field treatments. The optimum conditions of these two treatments were seed lot dependent. Seed germination and the membrane permeability (electrical conductivity of seed leachates) were tested after the treatments. Hydropriming increased the germination speed of all three seed lots, as well as the germination percentage of ‘HB128’. Electric field treatment enhanced the germination percentage in both ‘Bingo II’ (the low germination seed lot) and ‘HB128’, but had no effect on ‘Bingo I’ (the high germination seed lot). The electrical conductivity of ‘Bingo I’ and ‘Bingo II’ was significantly reduced by both hydropriming and electric field treatments. However, a slight increase in the electrical conductivity of ‘HB128’ was also observed.